Tooth loss and systemic diseases in the slovenian elderly population - Žmavc, Jurij Bojan (Zdravstveno varstvo, 2024)
Introduction: This study aimed to assess the prevalence of edentulism and tooth loss in the Slovenian elderly population, along with the associated risk factors, and investigate the association between systemic and oral health. Methods: The study included 445 individuals aged 65 or older (average age: 79.7±8.9 years). Data on preserved teeth, dental history, chronic diseases, and medications were collected through clinical examinations. Height and weight were recorded in order to calculate body mass index (BMI), and the education level was also collected. Chronic systemic diseases and medications were categorized. Statistical analysis was conducted using linear regression and nonparametric tests. Results: Participants had an average of 4.7±7.7 teeth, with no significant gender differences. Higher age (ß=- 0.185, p<0.001) and lower education level (p<0.001) were associated with fewer teeth, while higher BMI showed no correlation (ß=-0.085, p=0.325). Diabetes mellitus (p=0.031), cardiovascular diseases (p=0.025), and thyroid diseases (p=0.043) were inversely related to retained teeth. This inverse relationship also applied to individuals who recovered from malignancies, not including head and neck malignancies (p=0.019). No significant relationship was found between osteoporosis and the number of teeth (p=0.573). Notably, antidiabetic drug use was inversely related to the number of teeth (p=0.004), while analgesics showed a positive relationship (p=0.022). Conclusions: This study highlights the association between specific sociodemographic factors, chronic diseases, and retained teeth among elderly individuals in Slovenia. High edentulism rates among the elderly emphasize the need for enhanced preventive measures and risk factor management, particularly for high-risk groups like the elderly.
Keywords: brezzobost; edentulism; elderly population; sistemske bolezni; starostniki; systemic diseases